Investigating the Effectiveness of Programs on Health Financing Based on Audit Procedures - Ionel BOSTAN (Tehran University of Medical Sciences, 2016)
Background: The present paper focuses on approaching the context and the actual manner of applying a method, known to be efficient and with a solid scientific background, on the institutional level of healthcare in Romania. Methods: The analyses and correlations developed by the author have taken into account the latest editions of the journals and publications of these institutions, such as statistical papers, standards, procedural guidebooks, reports. Most of the data (easily identifiable in the electronic environment) have been selected to enable the subsequent further investigation. Results: The payments made in 2012 for the audited NHP1-4, have increased by 82 282.66 thousand € (39.2%) as compared to 2010, and by 50578.22 thousand € (20.9%) as compared to 2011. The amounts paid for NHP1-4 have had an ascending trend starting with 2010, but, during 2010-2012, as the contribution of the Ministry of Health from the state budget has decreased from 152590.66 thousand € to 95328.22 thousand €, CNAS's funding from the FNUASS resources has increased by 2.4 times. Conclusion: Following the analysis conducted on the NHP1-4, the findings based on representative samples are: (i) the specific legal standards related to the development of the NHP1-4, did not provide all the mechanisms that would ensure the certain procurement of medication and medical supplies as needed and did not ensure the efficient use of the allocated funds; (ii) clear discontinuities have been identified in the funding of NHP1-4, etc.   Keywords: Health network, Public health funding, National programmes, External audit